Aplicação para gerenciamento de missões empregando Veículos Aéreos não Tripulados (VANTs) em tomadas de imagens para a agricultura de precisão - Silva, Cleber dos Santos Medeiros da (2022)
Producers use systems based on Precision Agriculture (PA) to improve their productivity, the quality of their products, and their means of production. They use sensors for data acquisition, intelligent machines, and Unmanned Aerial Vehicles (UAVs), also known as drones, to capture images with high spatial resolution. Image processing can generate results such as production forecasting, identifying diseases and pests, and monitoring crop growth evolution, among other results. This project aims to create an application capable of managing, planning, and executing drone missions simply and intuitively for the farmer, enabling the execution of missions, sending captured images, planning flight dates based on crop and cultivating, sharing images with research groups for further processing, and obtaining results. The application was developed in three stages: 1 - an API responsible for managing information, results, and images; 2 - a web application provides user interaction with flight planning, sending images, and viewing results; 3 - and the application performs the execution of the mission by sending the routes and actions programmed for execution on the drone. Two missions were planned in the web application, and ten flights were performed in two test areas, both performed by the farmer using the developed application, generating results such as an orthomosaic, Digital Surface Model (DSM), and point cloud. Ten flights were successfully planned, executed, and stored in the application, showing that the developed application can assist the producer in carrying out drone flights, scheduling dates, and viewing the results. The application is available and integrated as a module in the AgDataBox platform.